PEMANFAATAN KOTORAN TERNAK KAMBING SEBAGAI PUPUK ORGANIK CAIR DI DESA KALONG LIUD - Sabania, Ikrimah Nur; Indriyani, Silvia; Gymnasti, Alista Dwis; Sutanto, Sutanto; Herlina, Eka; Warnasih, Siti (Universitas Nusa Bangsa, 2024)
The decrease in crop yields was caused by dry soil quality due to prolonged drought and excessive inorganic fertilizers in Kalong Liud village that were not adapted to plant needs, which could lead to a decrease in soil productivity. On the other hand, livestock waste (goat manure) that has not been managed optimally, often faced by livestock breeders and farmers, has good potential to help increase soil fertility on agricultural land at a reasonably low cost. The proposed solution to this problem is to switch to environmentally friendly organic fertilizer because it reduces the use of chemical substances. One of them is the use of goat manure, which contains high levels of nutrients such as phosphorus (P), nitrogen (N), and potassium (K). This community service activity aims to increase farmers' understanding that the use of organic fertilizer is a solution to overcome the problem of poor soil quality due to drought and excessive use of chemical fertilizers, as well as providing skills to farmers and breeders in Kalong Liud village in making liquid organic fertilizer from goat droppings. The method used includes the first stage of determining targets and implementing activities. The second stage of community outreach, Focus Group Discussion (FGD) and evaluation uses the test method, namely, comparing the pre-test and post-test results. The first stage of activities is determining targets, including surveys, outreach with breeders and farmers, observation, licensing, and activity planning, and then manufacturing liquid organic fertilizer. The second stage of activities carried out outreach with two topics: outreach to the community, discussions with the formed farmer groups, and evaluation through filling out questionnaires. After conducting community outreach and farmer group discussions, the results of this activity were that they understood how to make liquid organic fertilizer from goat manure and the dangers of using excess inorganic fertilizer on plants. After joint practice, the farmer group's understanding of liquid organic fertilizer obtained a post-test score of 98% of people who understood this program.